Potential Role Of Vitamin D Deficiency In Nonalcoholic Steatosis - SUDHA K,; RESHMA K; SOUPARNIKA (International Journal of Pharma and Bio Sciences, 2015)
Hypovitaminosis D is a wide spread and largely under recognizedpresent day epidemic. Since vitamin D undergoes activation in the liver, hepatic steatosis thought to be caused primarily due to insulin resistance can play a role in vitamin D deficiency. Hence the present study was conducted in 75 adult non diabetic patients in the age group of 25-55(45 males, 30 females) with hepatic steatosis. Liver function tests were estimated in the plasmaspectrophotometrically. Vitamin D was determined by ECLIA. Study groups included vitamin D deficient (group I), insufficient (group II) and sufficient groups (group III). Plasma ALT , ALP and total bilirubin levels were significantly higher in group I and II compared to group III patients. However, AST/ALT ratio was significantly higher groupIII compared to others. Plasma bilirubin and ALT showed significant negative correlation with vitamin D (r=-0.553,p=0.01) and AST/ALT ratio showed a positive correlation. The inverse association of vitamin D and hepatic markers attributes a possible hepatoprotective role of vitamin D. Patients with risk of impaired liver function need to be screened for vitamin D deficiency and its supplementation may prove beneficial.